A confirmatory factor analysis of the Observer Alexithymia Scale in treatment seeking alcohol-dependent patients. (December 2013) - Thorberg, Fred A.; Young, Ross M.; Sullivan, Karen A.; Lyvers, Michael; Hurst, Cameron P.; Tyssen, Reidar; Connor, Jason P.; Feeney, Gerald F. X.
<x xml:space="preserve">Abstract</x> Confirmatory factor analyses evaluated the factorial validity of the Observer Alexithymia Scale (OAS) in an alcohol-dependent sample. Observation was conducted by clinical psychologists. All models examined were rejected, given their poor fit. Given the psychometric limitations of the OAS shown in this study, the OAS may not be the most appropriate measure to use early in treatment among alcohol-dependent individuals.